Blockchain technology and AI‐facilitated polymers recycling: Utilization, realities, and sustainability. Issue 12 (19th September 2022) - Verma, Deepak; Okhawilai, Manunya; Dalapati, Goutam Kumar; Ramakrishna, Seeram; Sharma, Abhishek; Sonar, Prashant; Krishnamurthy, Satheesh; Biring, Sajal; Sharma, Mohit
Abstract: From the environmental perspective, efficient plastic utilization and its recyclability become significant issues that need to be resolved for deploying urban and sustainable technologies. It is estimated that approximately 400 million tons of plastic are produced each year for different applications. This number will be doubled by 2050, which is a serious problem. The primary issue that arises in a recycling process is associated with optimum supply chain management. The comprehensive and transparent supply chain methodologies will help stockholders to make conclusive policies and precise strategies. Transparency in supply chain management assists in captivating planning, pricing, purchasing, and inventory management decisions. Environmental sustainability requires recycling, which should have innovative concepts like Artificial Intelligence (AI) and Block‐chain Technology. Manual methods of sorting and segregating the waste have outdated and not much efficient. The inclusion of AI and Blockchain Technology brought a revolution by increasing the efficiency and accuracy of the recycling process. This critical review focused on recycling plastics and plastic waste using AI and Blockchain Technology. Various plastic regulation policies and AI utilization for plastic recycling are discussed. An overview of the blockchain and its classification for waste management or plastic recycling has been discussed. The utilization of Blockchain Technology for a plastic circular economy, its types, and critical benefits has also been systematically demonstrated. Abstract :